EMI and Intercultural Competence at University of Alcalá: The case of the Master's Degree in Teacher Training - Isabel De la Cruz Cabanillas; Cristina Tejedor-Martínez (Universitat Jaume I. Department of English Studies, 2021)
The use of English as a Medium of Instruction to teach subjects other than English is widely spread across European higher education institutions. The University of Alcalá has been working on the implementation of English-Medium Instruction (EMI) for decades now. The internationalisation process accounts for the increasing number of studies both at undergraduate and postgraduate levels taught in English. The response of international students has been positive considering the University of Alcalá one of their favourite Spanish destinations. The interaction of local and foreign students evidences the need to raise awareness towards the intercultural competence as part of the Master's Degree in Teacher Training, so that learners will feel comfortable in a different language and culture and contribute significantly not only to the labour market but also to dialogue and living together. In this article, the authors report on how this is done in one of the compulsory courses of this specific Master's Degree: Complementary Training in English Studies.